Characteristics of Facilitated Critical Thinking in Speaking for Maritime English Improvement - Faisal Rachman, Natriya; Oktavia, Wahyuni; Kustanto, Jaka Septian (Tell : Teaching of English Language and Literature Journal, 2024)
The maritime industry, a cornerstone of global trade and commerce, relies heavily on effective communication, primarily through Maritime English. Ensuring safety, operational efficiency, and regulatory compliance on international waters necessitates proficiency in this standardized form of English. Despite its critical role, many maritime professionals struggle with Maritime English, especially speaking and critical thinking skills. This study explores how facilitated critical thinking in speaking can enhance Maritime English proficiency. Facilitated critical thinking involves instructional strategies that promote analysis, synthesis, and evaluation of information through interactive dialogues, problem-solving tasks, reflective practice, and collaborative learning. This study employs a mixed-methods approach, including quantitative and qualitative phases, to examine these strategies among maritime students and professionals. Results from paired samples statistics, correlations, and t-tests indicate significant improvements in speaking proficiency and critical thinking skills following the intervention. The findings suggest that integrating critical thinking into language instruction effectively addresses the unique challenges maritime professionals face, ultimately enhancing communication and safety in the maritime industry